The diary of a provincial lady - E. M. Delafield (London Virago, 1984)
The goal of the provincial lady is to maintain 'niceness', whether it be in the home, relationships or personal behaviour. 'The Diary of a Provincial Lady' first published in the 1930s is a witty celebration of the suburban British housewife
Keywords: story